Commitment to Church of the Poor in Service at the Cinta Orang Miskin Foundation Surabaya - Saefnat Saetban; Agustinus Faot (Jurnal Didaskalia, 2019)
Research on the commitment of the poor at the Cinta Orang Miskin Foundation is motivated by the reality of academic and practical gaps. From an academic perspective, researchers have never found the commitment of the poor at the Cinta Orang Miskin Foundation, even though the number of poor people is committed for the church to thrive. Currently the number reaches 1,300 people. On a practical level, this research wants to explore the decisions of these poor people to find out their commitment to involvement in the Cinta Orang Miskin Foundation (COM), which is served by Pastor Gunawan Setiadarma in Surabaya, East Java, which has experienced significant growth from 23 congregations to 1,300 people. The problem of poverty is a problem that is being faced by the nation (nations in the world in general. The Indonesian nation itself cannot be separated from the poverty problem. The economic crisis that occurs within the Indonesian nation has an impact on all aspects of people's lives. It can be seen from the existence of people who live in poverty, live in slum environments, and the number of children (street children who are scattered in cities (cities in Indonesia). During this economic crisis, the number of street children in Indonesia increased drastically.